Human serum influences functional plasticity and transcriptomic landscape of γδ T cells in vitro - Pinot, Lorraine; Zhumadilova, Zhibek; Saßor, Aylin; Sagar,; Villacorta Hidalgo, José (Frontiers in Immunology, 2026)
γδ T cells are emerging as a promising platform for adoptive cell therapy due to their ability to recognize tumors independently of MHC and their minimal risk of causing graft-versus-host disease. While serum-supplemented media have traditionally been used for T cell expansion, they can present limitations including xenogeneic contaminants and batch variability. These issues can compromise T cell phenotype, function, and clinical reproducibility. In this study, we evaluated the impact of human serum on the expansion, phenotype, function, and transcriptomic landscape of Vγ9Vδ2 γδ T cells cultured with zoledronate and cytokines under serum-free versus serum-containing conditions. We evaluated cytotoxicity against triple-negative breast cancer cell lines, activation and checkpoint marker expression, and cytokine secretion. Single-cell RNA and TCR sequencing revealed consistent differentiation trajectories across donors in both conditions and gene expression dynamics during a two-week expansion period. Our results show that serum-free culture supports robust γδ T cell expansion with higher purity and an activated phenotype marked by increased activation markers and reduced checkpoint receptor expression. Serum-free expanded cells displayed comparable or enhanced cytotoxicity and cytokine production, especially IFN-γ. TCR repertoire diversity was preserved without clonal skewing in both conditions. Furthermore, re-exposure to serum late in culture had minimal influence on γδ T cell functionality. These findings demonstrate the feasibility and advantages of serum-free expansion protocols for Vγ9Vδ2 γδ T cells, offering improved consistency, safety, and therapeutic potential.